2016
DOI: 10.1371/journal.pone.0158653
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Differentially Expressed Tissue-Type Plasminogen Activator in Experimental Autoimmune Encephalomyelitis: Implications for Multiple Sclerosis

Abstract: Tissue type plasminogen activator (t-PA) has been implicated in the development of multiple sclerosis (MS) and in rodent models of experimental autoimmune encephalomyelitis (EAE). We show that levels of t-PA mRNA and activity are increased ~4 fold in the spinal cords of wild-type mice that are mice subjected to EAE. This was also accompanied with a significant increase in the levels of pro-matrix metalloproteinase 9 (pro-MMP-9) and an influx of fibrinogen. We next compared EAE severity in wild-type mice, t-PA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…Some reports indicate that tPA −/− mice present earlier and more severe disease that their WT counterparts, suggesting a protective role of tPA [12,31,32]. Other studies, including the present one, argue for a deleterious effect of tPA [11].…”
Section: Discussionsupporting
confidence: 47%
“…Some reports indicate that tPA −/− mice present earlier and more severe disease that their WT counterparts, suggesting a protective role of tPA [12,31,32]. Other studies, including the present one, argue for a deleterious effect of tPA [11].…”
Section: Discussionsupporting
confidence: 47%
“…tPA is implicated in MS development and is up-regulated fourfold when EAE is induced. It seems to play a protective role in EAE, as tPA-deficient mice have an earlier onset and increased severity of demyelination (East et al, 2005; Dahl et al, 2016), likely because tPA is necessary to clear fibrin deposits on axons damaged during EAE progression. Axonal damage is a crucial contributor to MS progression, and fibrinogen has been shown to be a critical regulator of microglial activation and axonal damage in EAE (Davalos and Akassoglou, 2012).…”
Section: Plasminogen Plays a Role In The Development Of Many Pathologiesmentioning
confidence: 99%
“…The role of tPA in the T cell-mediated EAE model is still a matter of debate. Previous reports demonstrate an increase in tPA activity in EAE [56] , [57] . In addition, expression of tPA and its inhibitor PA1 transcripts are found in the sites of tissue damage and neuroinflammation suggesting an involvement of this serine protease in the EAE physiopathology [58] .…”
Section: The Role Of Tpa In T Cell Activitymentioning
confidence: 77%
“…Initially, Lu et al described that tPA - / - developed a more severe form of EAE but with a delayed onset in the disease [57] . Although most studies corroborated this finding and showed a protective role of tPA [8] , [56] , [59] , others reported a detrimental function of tPA in the pathogenesis of EAE with either tPA deficiency which results in a less severe form of EAE or tPA administration that increases the severity of EAE [9] , [51] . These inconsistencies between several studies may be attributed to the differences in the experimental protocols including myelin antigen doses, sex and age of the animals or the number of immunizations/boosts.…”
Section: The Role Of Tpa In T Cell Activitymentioning
confidence: 89%